2015
DOI: 10.1073/pnas.1504131112
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal fluxes of carbonyl sulfide in a midlatitude forest

Abstract: Carbonyl sulfide (OCS), the most abundant sulfur gas in the atmosphere, has a summer minimum associated with uptake by vegetation and soils, closely correlated with CO 2 . We report the first direct measurements to our knowledge of the ecosystem flux of OCS throughout an annual cycle, at a mixed temperate forest. The forest took up OCS during most of the growing season with an overall uptake of 1.36 ± 0.01 mol OCS per ha (43.5 ± 0.5 g S per ha, 95% confidence intervals) for the year. Daytime fluxes accounted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
133
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(148 citation statements)
references
References 59 publications
13
133
2
Order By: Relevance
“…This means that vegetative uptake of COS can continue during the night if stomata are not completely closed . Caird et al (2007) showed that nighttime stomatal conductance exists in a wide variety of plant species and several studies report nighttime depletion of COS mole fractions (White et al, 2010;Belviso et al, 2013;Commane et al, 2013Commane et al, , 2015Berkelhammer et al, 2014;Maseyk et al, 2014;Wehr et al, 2017). The measurements presented in White et al (2010), Maseyk et al (2014), Berkelhammer et al (2014) and Wehr et al (2017) indicated that nighttime ecosystem COS fluxes were indeed dominated by the vegetation, and not by the soil.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…This means that vegetative uptake of COS can continue during the night if stomata are not completely closed . Caird et al (2007) showed that nighttime stomatal conductance exists in a wide variety of plant species and several studies report nighttime depletion of COS mole fractions (White et al, 2010;Belviso et al, 2013;Commane et al, 2013Commane et al, , 2015Berkelhammer et al, 2014;Maseyk et al, 2014;Wehr et al, 2017). The measurements presented in White et al (2010), Maseyk et al (2014), Berkelhammer et al (2014) and Wehr et al (2017) indicated that nighttime ecosystem COS fluxes were indeed dominated by the vegetation, and not by the soil.…”
Section: Introductionmentioning
confidence: 94%
“…Besides restricting COS as a GPP tracer to light conditions, the leaf relative uptake ratio (LRU), which is the normalized ratio between COS and CO 2 fluxes, can be expected to increase when GPP becomes zero around sunrise and sunset while at the same time COS is continuously being taken up by vegetation. So far, only Stimler et al (2011) have showed the light dependence of LRU from leaf-scale measurements and Maseyk et al (2014) and Commane et al (2015) observed a light dependence in the ratio of ecosystem fluxes of COS and CO 2 . Other studies have focused on LRU values under high-light conditions (e.g., Sandoval-Soto et al, 2005;Berkelhammer et al, 2014).…”
Section: Effect Of Nighttime Cos Fluxes On Gpp Derivationmentioning
confidence: 99%
“…The available observations are limited in time and do not cover tropical ecosystems, which contribute almost 60% of global GPP (Beer et al, 2010). The only study reporting year-round OCS flux measurements is from a mixed temperate forest, which was a sink 15 for OCS with a net flux of -4.7 pmol m -2 s -1 during the observation period (Commane et al, 2015).…”
Section: Terrestrial Ecosystemsmentioning
confidence: 99%
“…Since ocean COS emissions are geographically separated from the terrestrial COS sinks (leaf and soil), and anthropogenic emissions are usually concentrated as point sources, the spatial separation of dominant COS sources and sinks enables us to constrain land COS fluxes, and hence photosynthetic carbon uptake, from atmospheric COS observations (Campbell et al, 2008;Berry et al, 2013;Hilton et al, 2015). However, for the use of COS as a photosynthetic tracer, soil COS flux, which is unrelated to photosynthesis, needs to be understood and separated from the ecosystem COS flux that is the sum of leaf and soil fluxes Commane et al, 2015;Wehr et al, 2017).…”
mentioning
confidence: 99%